Sistem Antrian Pelanggan Menggunakan Metode Jackson Network Queue - Mukhamad Niamaskur; Andi Widiyanto; Agus Setiawan (Jurnal Sistem Komputer dan Informatika (JSON), 2023)
Information systems can be applied in various fields either as the main means or to increase productivity or service quality. One of the uses of technology is that it is used as a means to make it easier for customers to place orders which aims to avoid queues that are too long. Setia Car Spare Parts Store is a provider of car spare parts that has many customers which sometimes makes the customer queue too much. This sometimes makes customers, especially new customers, impatient to queue. To make the queue more orderly, a queuing system will be built to maximize service and increase customer satisfaction which is calculated using the Jackson method. This method was chosen to calculate the time that is considered in accordance with what the customer expects. The queuing system applied to the system built is a single channel FIFO. From the results of system testing carried out, the application of a queuing system with online ordering by applying the Jackson method can enable employees to serve 48 customers in a day with an average of 15 minutes of service time. These results are more when compared to offline services where each employee can only serve 41 customers with an average service time of 17.56 minutes.